Rock Jaw. Book 5 : master of the eastern border - Smith, Jeff, 1960 February 27- (Smith, Jeff, 1960 February 27- Bone, 2007)
Fone and Smiley Bone encounter complications in the form of Rock Jaw, an enormous mountain lion, and baby animals orphaned by rat creature attacks as they journey through the wilderness with a lost rat creature cub they are returning to the mountains.